Study on the detection and suppression methods of carbon laying defects in auto fiber placement (AFP) process - Yixuan Xie; Zhiqiang Liu; Yinqi Li; Yueyue Zong (Advanced Manufacturing)
This paper proposes an optimal control strategy for process parameters aimed at addressing layup defects, achieving defect recognition and localization, and maintaining temperature stability on the actual layup surface. Infrared thermography is employed to identify defects during the carbon fiber layup process, and by integrating path control, the identification and localization of defects during the layup are effectively achieved. The minimum edge detection rate on both sides of a single layer reaches 94.3%, and the interlayer gap measurement is below 10%. Considering that temperature instability on the layup surface can lead to defects, a dynamic temperature control model has been established, and the infrared lamp’s temperature rise coefficient is determined, reducing defects caused by temperature fluctuations during the layup process. The results indicate that infrared thermography technology is feasible for the detection and reduction of defects in CFRP composites.